Determinants of non-Hodgkin’s lymphoma at Felegehiwot specialized hospital, North West Ethiopia: A case-control study - Chekol, Dessalegn (PLoS One, 2020)
BACKGROUND: The global burden of cancer continues to increase largely because of the aging and growth of the world population alongside an increasing adoption of cancer-causing behaviors. Hence, the purpose of this study was to identify determinants of Non-Hodgkin lymphoma cancer among individuals who diagnosed at the Felegehiwot specialized hospital, North West Ethiopia, 2019. METHODS: An institution-based unmatched case-control study was conducted at the Felegehiwot Specialized hospital from December 2018 up to June 2019. The sample size calculated using the two-population proportion formula. The final sample size was 486, (162 cases and 324 controls). The simple random sampling method was employed to catch up with the estimated samples. The collected data entered into the Epi-data version 3.1 software and analyzed using SPSS version 21 software. Descriptive statistics computed. Simple logistic analysis was run (at 95% CI and p-value < 0.05) to identify the determinants of non-Hodgkin’s lymphoma. RESULT: A total of 486 patients participated. Nearly one-third of the cases and controls were in the age group of 46–60 years. About 90% of cases and 91% of controls were orthodox Christian. Monthly income of ≤28 dollars (AOR = 2. 73, 95%CI: 1. 8, 4.2), male sex (AOR = 1. 8, 95%CI: 1.2, 2.8), ever had chemical exposure, (AOR = 11. 9, 95%CI: 7.6, 18.8), no regular physical exercise (AOR = 15. 5, 95%CI: 5.7, 42.3), and having hypertension [AOR = 0. 03; 95%CI:0.005, 0.2), lung disease (AOR = 0. 2; 95%CI: 0.06, 0.7), and chronic kidney and cardiac diseases (AOR = 0. 06; 95%CI: 0.01, 0.2) were the determinants of non-Hodgkin’s lymphoma. CONCLUSIONS: The findings in this study suggest that having a low monthly income, being male sex, ever had chemical exposure, not engaged in regular physical exercise, and being diabetic were the determinants of non-Hodgkin’s lymphoma.